2023
DOI: 10.1371/journal.pone.0283593
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early nutrition and feeding route on clinical outcomes of neurocritically ill patients

Abstract: Early proper nutritional support is important to critically ill patients. Nutritional support is also associated with clinical outcomes of neurocritically ill patients. We investigate whether early nutrition is associated with clinical outcomes in neurocritically ill patients. This was a retrospective, single-center, observational study including neurosurgical patients who were admitted to the intensive care unit (ICU) from January 2013 to December 2019. Patients who started enteral nutrition or parenteral nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Thus, in previous studies, patients who received early nutritional support were more likely to have mild disease severity, or at least no worse than those who received late nutrition support. For instance, one study [ 4 ], including 1353 neurocritically ill patients, reported that early enteral nutrition reduced the risk of in-hospital mortality and infectious complications. In this study [ 4 ], early nutrition support was defined as enteral or parenteral nutrition within 72 h after ICU admission.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in previous studies, patients who received early nutritional support were more likely to have mild disease severity, or at least no worse than those who received late nutrition support. For instance, one study [ 4 ], including 1353 neurocritically ill patients, reported that early enteral nutrition reduced the risk of in-hospital mortality and infectious complications. In this study [ 4 ], early nutrition support was defined as enteral or parenteral nutrition within 72 h after ICU admission.…”
mentioning
confidence: 99%
“…For instance, one study [ 4 ], including 1353 neurocritically ill patients, reported that early enteral nutrition reduced the risk of in-hospital mortality and infectious complications. In this study [ 4 ], early nutrition support was defined as enteral or parenteral nutrition within 72 h after ICU admission. Compared to the early nutrition support group, the APACHE II score on ICU admission (8.3 ± 7.7 vs. 6.13 ± 5.5, p < 0.001), the proportion of patients receiving mechanical ventilation (67.3% vs. 53.9%, p < 0.001) and vasopressors use (16.5% vs. 11.7%, p = 0.033) were significantly higher in the late nutrition support group.…”
mentioning
confidence: 99%